Sistem Informasi Penerimaan Peserta Didik Baru Smk Sakti Gemolong Berbasis Web Responsive Dengan Html 5 Dan Css 3 - Riza, Prastica Putri; , Gunawan Ariyanto, Ph.D (2016)
Sakti Gemolong Vocational High School, one of school opening class counted 18 classes and 800 students each year. From big enough students requirement, Miraculous system PPDB Gemolong Vocational High School still using manual system, so that PPDB committee require extra activity and time which by dozens. To fulfill the requirement hence writer give the contribution to make the system PPDB base on the web responsive. Where this website could be accomodate the appearance from various devices like laptop, tablet, and also smartphone expected could be lighten PPDB committee performance in serving participant candidate educated and facilitate the participant candidate educated to register him or her self anywhere and whenever. Making of Vocational High School Miraculous PPDB system information Gemolong by online base on the web responsive by using Framework Codeigniter consisted by HTML5, PHP5 and Bootstrap consisted of CSS3 and Javascript, while database was used Mysql. PPDB system existence base on the web responsive couldbe giving the amenity of school to be able to map was earlier than enthusiast every majors, also give the amenity from students candidate to do registration more early and don't have to be direct to location go to school.